Molecular sequence analysis of prokaryotic diversity in the middle and outer sections of the Portuguese estuary Ria de Aveiro - Henriques, I. S. (2004)
Construction of 16S rDNA libraries was undertaken to examine the structure of free-living bacterial communities in the estuarine system Ria de Aveiro, Portugal. Samples were collected in April 2002, from two sites representing marine (station N1) and brackish (station I6) water zones. Clones were characterized by RFLP patterns and sequence analysis of representative clones revealed that both libraries were clearly dominated by α-proteobacteria, followed by γ-proteobacteria and β-proteobacteria. Clones affiliated with the δ-proteobacteria, Verrucomicrobia, Bacteroidetes and Actinobacteria were exclusive of station I6 and sequences related to the Firmicutes were only found in station N1. Sequences retrieved are included in only a few major bacterial divisions and in general, shared a high degree of homology with sequences deposited in nucleotide databases, and recovered from aquatic environments of diverse geographic regions. Differences between the two sites may reflect adaptation to different environmental conditions, especially salinity. The pattern of prokaryotic diversity is comparable to other coastal and estuarine environments previously studied.